2014
DOI: 10.1016/j.ophtha.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Medication and Intraocular Pressure in a British Population

Abstract: ObjectiveTo determine the association between systemic medication use and intraocular pressure (IOP) in a population of older British men and women.DesignPopulation-based, cross-sectional study.ParticipantsWe included 7093 participants from the European Prospective Investigation into Cancer–Norfolk Eye Study. Exclusion criteria were a history of glaucoma therapy (medical, laser, or surgical), IOP asymmetry between eyes of >5 mmHg, and missing data for any covariables. The mean age of participants was 68 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 44 publications
(41 reference statements)
5
60
1
13
Order By: Relevance
“…Thus, hypertension was defined as a patient receiving ≥2 antihypertensive compounds. Because previous studies have shown a decreased risk of glaucoma in patients treated with systemic β-blockers or calcium channel inhibitors, 16,23,[35][36][37] it seems reasonable to interpret the present observed reduction of the risk of developing glaucoma in patients treated with antihypertensive as a causal effect of particular antihypertensive drugs. …”
mentioning
confidence: 48%
“…Thus, hypertension was defined as a patient receiving ≥2 antihypertensive compounds. Because previous studies have shown a decreased risk of glaucoma in patients treated with systemic β-blockers or calcium channel inhibitors, 16,23,[35][36][37] it seems reasonable to interpret the present observed reduction of the risk of developing glaucoma in patients treated with antihypertensive as a causal effect of particular antihypertensive drugs. …”
mentioning
confidence: 48%
“…A populationbased study has investigated the association between the use of common systemic medications and IOP. 21 According to the results of that study, the use of systemic β-blockers and nitrates were independently associated with lower IOP. However, in the present study we did not find any effects of systemic β-blocker use on IOP decrease during HD.…”
Section: Discussionmentioning
confidence: 93%
“…In another report, systemic beta-receptor antagonists and nitrates were associated with a lower IOP when effects of blood pressure were factored out. 104 In addition, retrospective analysis of patient data indicate that intake of statins is protective for glaucoma. 105 In the absence of randomized large-scale trials, it is, however, difficult to fully explore the impact of systemic therapies on glaucoma incidence and progression, because a disease-modifying effect of the underlying disease can never be ruled out.…”
Section: Systemic Therapiesmentioning
confidence: 99%